Family History of Early Infant Death Correlates with Earlier Age at Diagnosis But Not Shorter Time to Diagnosis for Severe Combined Immunodeficiency - Luk, Anderson Dik Wai; Lee, Pamela P.; Mao, Huawei; Chan, Koon-Wing; Chen, Xiang Yuan; Chen, Tong-Xin; He, Jian Xin; Kechout, Nadia; Suri, Deepti; Tao, Yin Bo; Xu, Yong Bin; Jiang, Li Ping; et al. (Frontiers in Immunology, 2017)
Background Severe combined immunodeficiency (SCID) is fatal unless treated with hematopoietic stem cell transplant. Delay in diagnosis is common without newborn screening. Family history of infant death due to infection or known SCID (FH) has been associated with earlier diagnosis. Objective To identify the clinical features that affect age at diagnosis and time to diagnosis of SCID. Methods From 2005 to 2016, 147 SCID patients were referred to the Asian Primary Immunodeficiency Network (APIN). Patients with genetic diagnosis, age at presentation and age at diagnosis were selected for study. Results Eighty-eight different SCID gene mutations were identified in 94 patients, including 49 IL2RG mutations, 12 RAG1 mutations, 8 RAG2 mutations, 7 JAK3 mutations, 4 DCLRE1C mutations, 4 IL7R mutations, 2 RFXANK mutations and 2 ADA mutations. 29 mutations were previously unreported. Eighty-three of the 94 patients fulfilled the selection criteria. Their median age at diagnosis was 4 months and time to diagnosis 2 months. The commonest SCID was X-linked (n= 57). 29 patients had a positive FH. Candidiasis (n= 27) and BCG infection (n= 19) were the commonest infections. The median age for candidiasis and BCG infection documented were 3 and 4 months respectively. The median absolute lymphocyte count (ALC) was 1.05 x 109/L with over 88% patients below 3 x 109/L. Positive FH was associated with earlier age at presentation by 1 month (p= 0.002) and diagnosis by 2 months (p= 0.008), but not shorter time to diagnosis (p= 0.494). Candidiasis was associated with later age at diagnosis by 2 months (p= 0.008) and longer time to diagnosis by 0.55 months (p= 0.003). BCG infections were not associated with age or time to diagnosis. Conclusion FH was useful to aid earlier diagnosis but was overlooked. Similarly, typical clinical features of SCID were not recognized by clinicians to shorten the time to diagnosis. We suggest that lymphocyte subset should be performed for any infant with one or more of the 4 following clinical features: FH, candidiasis, BCG infections and ALC below 3 x 109/L.